Unix™ Systems Programming: Communication, Concurrency, and Threads - Robbins, Kay A. (Prentice Hall PTR, 2011)
This completely updated classic (originally titled Practical UNIX Programming) demonstrates how to design complex software to get the most from the UNIX operating system. UNIX Systems Programming provides a clear and easy-to-understand introduction tothe essentials of UNIX programming. Starting with short code snippetsthat illustrate how to use system calls, Robbins and Robbins movequickly to hands-on projects that help readers expand their skill levels.